(untitled) (Research, Society and Development, 2023)
Nowadays, the compromising of the immune system has been discussed and theorized with the significant increase of autoimmune diseases. These diseases have multifactorial causes and can be caused by genetic fitness, exposure to xenobiotics, high levels of stress, infectious agents, poor quality sleep, drug and/or alcohol use, and tobacco dependence. The disease is triggered by one or a combination of more factors. Given this, the objective of the work was to understand the importance of integrative nutrition in patients with autoimmune diseases, from a literature search in scientific databases such as Pubmed, ScieLO, EBSCO and CAPES, considering articles published between 2012 and 2023, in Portuguese and English languages, being excluded those that did not fit the proposed theme and animal studies. The study sought to relate the multiple factors that cause aggravation or remission of the disease in the individual, as well as its numerous causes of irritation, with nutritional intervention measures that reduce inflammation, support the immune system, and restore the patient’s health balance for better well-being. It has been found that the patient with autoimmune disease requires treatment in a holistic way, where professionals are attentive to their totality. Care needs to go beyond drugs to control the disease; after all, aligning mind and body is essential for the remission of the disease, since its manifestation involves more than genetics and inflammation.